2022
DOI: 10.1016/j.ajogmf.2022.100569
|View full text |Cite
|
Sign up to set email alerts
|

The impact of response to iron therapy on maternal and neonatal outcomes among pregnant women with anemia

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
(43 reference statements)
0
13
0
2
Order By: Relevance
“…Despite the small sample size of our study, a recent study reported that patients exposed to iron supplementation(ferrous sulfate, ferrous gluconate, ferrous fumarate, and ferrous glycinate) experienced reduced odds of preeclampsia and/or PTB. [30] In contrast to sertraline and ferrous sulfate, the signal we observed for acyclovir was misleading. According to CDC treatment guidelines, [25] acyclovir is recommended for administration at 36 weeks of gestation for patients with genital herpes.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Despite the small sample size of our study, a recent study reported that patients exposed to iron supplementation(ferrous sulfate, ferrous gluconate, ferrous fumarate, and ferrous glycinate) experienced reduced odds of preeclampsia and/or PTB. [30] In contrast to sertraline and ferrous sulfate, the signal we observed for acyclovir was misleading. According to CDC treatment guidelines, [25] acyclovir is recommended for administration at 36 weeks of gestation for patients with genital herpes.…”
Section: Discussionmentioning
confidence: 65%
“…Despite the small sample size of our study, a recent study reported that patients exposed to iron supplementation(ferrous sulfate, ferrous gluconate, ferrous fumarate, and ferrous glycinate) experienced reduced odds of preeclampsia and/or PTB. [30]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Despite American College of Obstetricians and Gynecologists' recommendations for routine complete blood cell count screening, there are screening inconsistencies in clinical settings. 13,41 Many believe that national guidelines reflect outdated evidence on anemia in pregnancy and promulgate inequalities by race and ethnicity. 9,34,42 Our data support a strong correlation between antepartum anemia and SMM; antepartum anemia drives SMM more than nontransfusion SMM for every racial and ethnic group.…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency is the most common cause of anemia and is the most widespread nutritional disorder in the world [3,4]. Anemia had the potential risk of increasing preterm birth in addition to many other maternal diseases during and after pregnancy [5]. Since anemia is the most common diagnosis among pregnant women [6], it could be significantly associated with preterm labor as well as other comorbidities [7].…”
Section: Introductionmentioning
confidence: 99%